Efektivitas Metode Latihan Interval dalam Meningkatkan Daya Tahan Atlet Anggar - Irwandi Irwandi (Jurnal Humaniora Pendidikan (JHP), 2026)
This study aimed to examine the effectiveness of interval training in improving the endurance of fencing athletes. A quantitative approach with a one-group pretest–posttest design was employed. The participants consisted of 24 fencing athletes, selected using a total sampling technique. The interval training program was conducted over eight weeks, with three training sessions per week. Athletes' endurance was assessed using the Multistage Fitness Test (MFT) to estimate maximal oxygen uptake (VO₂max). Data were analyzed using descriptive statistics, the Shapiro–Wilk normality test, and a paired-samples t-test with IBM SPSS Statistics 29 at a significance level of 0.05. The findings revealed that the mean VO₂max increased from 45.18 ± 2.97 ml·kg⁻¹·min⁻¹ at pretest to 49.48 ± 3.12 ml·kg⁻¹·min⁻¹ at posttest. The paired-samples t-test indicated a significant improvement in endurance (p = 0.000; p < 0.05) following the interval training program. Furthermore, the calculated Cohen's d value of 1.56 indicated a large effect size, while the percentage improvement reached 9.52%. These findings suggest that interval training effectively enhances aerobic capacity by promoting physiological adaptations that improve cardiovascular efficiency and oxygen utilization during high-intensity activities. Therefore, interval training can be recommended as an effective conditioning strategy for improving endurance and supporting competitive performance in fencing athletes